Nausea and Desire: affective access to the original pre-subjective structure in the philosophy of Emmanuel Levinas - Campos Salvaterra, Valeria (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Affectivity is central to the work of Emmanuel Levinas for being the starting point for ethics,the genetic moment of moral phenomenon in general and subjective ethical experience. But it can also be read as a comprehensive moment that opens the way to the deeper subjective structures —those that are fundamental to ethics as Levinas understands it—, allowing thus a reflection about human existence and, especially, about human transcendence to the otherness of the other man. This paper aims to explore this second phenomenological function of affection to discover new ways in which Levinas understands human subjectivity.